Comparative Study of FT-IR Profiles Preparation of Nano-Hydrogel Combination of Soursop Extract and Zinc - Urmatul Waznah; Achmad Vandian; Eko Mugiyanto; Nuniek Nizmah Fajriyah (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Nanoparticles delivery system of of herbal preparations and their combinations has received more attention from scientists recently. This combination might lead to chemical reactions among the added constituents. This study aims to compare the FT-IR profile of Carbopol-940 base before and after the addition of soursop extract and zinc oxide nanoparticle. The preparation is made by mixing the base with Annona muricata nano-extracts and nano-zinc. Extraction was carried out by cold maceration of A. muricata leaves in ethanol and then convert into nanoparticles with the assisting of Chitosan biopolymer by ionic gelation method. Nano-zinc is formulated by precipitating zinc acetate by sodium hydroxide. The two nano-formulas were then mixed up into the Carbopol-940 gel matrix. The results show a shift in the profile of Carbopol-940 at a wavelength of 1500 nm to 1700 nm. From the results, it can be seen that there is no difference in the physical characteristics of the base with the addition of the two nano active ingredients. Further research needs to be done to confirm this finding.